2019
DOI: 10.1155/2019/2168603
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Activity of Medicinal Plants Used among the Cakchiquels in Guatemala for the Treatment of Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is a major health problem worldwide. In this condition, the organism can produce insulin but becomes resistant to it; thus the insulin is ineffective. High blood glucose levels are a result of insulin resistance and insulin deficiency; they produce diabetes-associated complications such as kidney failure, blindness, cardiovascular disease, and lower-limb amputation. In Guatemala, there were over 752.700 cases of the disease in 2017 with prevalence of 8.4 (IDF, 2017). The use of plants for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…To determine whether the infusion used at the traditional dose produces a hypoglycemic effect in the fasting state, we performed an acute experiment [ 16 ]. In brief, hyperglycemic animals were divided into four groups (1–4) of six rats each: (1) a normal control group in which each rat received 1.5 mL of physiological NaCl solution by gavage (vehicle); (2) a hyperglycemic control group in which each rat received 1.5 mL of physiological NaCl solution; (3) a positive control group in which each rat received the standard oral hypoglycemic agent glibenclamide (Euglucon®) at the dose of 5 mg/kg b.w.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether the infusion used at the traditional dose produces a hypoglycemic effect in the fasting state, we performed an acute experiment [ 16 ]. In brief, hyperglycemic animals were divided into four groups (1–4) of six rats each: (1) a normal control group in which each rat received 1.5 mL of physiological NaCl solution by gavage (vehicle); (2) a hyperglycemic control group in which each rat received 1.5 mL of physiological NaCl solution; (3) a positive control group in which each rat received the standard oral hypoglycemic agent glibenclamide (Euglucon®) at the dose of 5 mg/kg b.w.…”
Section: Methodsmentioning
confidence: 99%
“…ese phenolics were 10 phenolic acids (quinic acid, gallic acid, protocatechuic acid, chlorogenic acid, 4-O-caffeoylquinic acid, syringic acid, caffeic acid, p-coumaric acid, trans-ferulic acid, and trans-cinnamic acid); 5 flavones (apigenin, luteolin, cirsiliol, cirsilineol, and acacetin); 2 flavonols (quercetin and kaempferol); 2 flavan-3-ols ((+)-catechin and epicatechin); 2 flavonol glycosides (rutin and quercitrin); 2 flavone glycosides (apigenin-7-Oglucoside and naringin); and 1 flavanone (naringenin). For derivative fractions of MeOH crude extract, 19 [100] reported that ten phenolic compounds, five isoflavones, and five flavones were characterized and performed by applying LC-DAD-ESI/MSn to three different extracts obtained from infusion, decoction, and maceration in hydroethanolic mixtures of Algerian E. alata.…”
Section: Recent Applications Of High-resolution Mass Spectrometry For Ephedra Extract Characterizationmentioning
confidence: 99%
“…It is estimated that over 200,000 primary and secondary metabolites may be present in the plant kingdom [11][12][13][14][15]. Medicinal plant is the product of long-term medical practice worldwide, with the advantages of outstanding curative properties and less side effects [16][17][18][19][20][21]. Containing many natural products and their derivatives of therapeutic value, medicinal plants are considerate as main source of remedies able to protect human body against diseases.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, various authors have demonstrated that H. patens has antidiabetic and hypoglycemic activity. Andrade-Cetto et al 24 . postulated that the hypoglycemic activity of this plant is due to the inhibition of glucosidase; however, we found that none of the extracts inhibited glucosidase at concentrations below 330 µg/mL, which was the maximum concentration evaluated.…”
Section: Discussionmentioning
confidence: 99%